National Insurance Act, 1911 (leaflet) (London : National Health Insurance Commission (England))
1912-06 1912 1910s 4 pages 4 MEMBERSHIP OF AN APPROVED SOCIETY. N.B. — It is of the greatest importance to every employed man or woman that he or she should join an Approved Society without delay, and so avoid becoming a Deposit Contributor. SOCIETIES WHICH ARE OR WILL BE APPROVED.— All kinds of Societies, such as Friendly Societies, Trade Unions, Provident Societies, Dividing Societies, Collecting Friendly Societies, and Industrial Assurance Companies are becoming Approved Societies themselves or forming Sections for the administration of the Insurance Act, and new Societies may be formed for the same purpose. If an insured person does not join a Society, he will have to become a Deposit Contributor. A Deposit Contributor ceases to have benefits when the actual contributions paid by himself and his employer, together with the State grant, have been drawn out, but a member of a Society can go on drawing benefits from the funds of the Society. A Deposit Contributor must not be confused with a Post Office Savings Bank Depositor. The two have no connection at all with each other. LIST OF OFFICIAL EXPLANATORY LEAFLETS. No. 1. Questions and Answers for Society Officials. No. 10. Sickness and Disablement Benefits. No. 2. Questions and Answers for Members of Friendly Societies. No. 11. How to become Insured. No. 11A. How to become Insured. Women. No. 3. Questions and Answers for Members of Dividing Societies and Slate Clubs. No. 12. Questions and Answers. Finance. No. 4. Who will be insured. No. 13. The Position of small Societies under the Act. No. 5. Advantages of joining An Approved Society. No. 14. Friendly Society Contributions before and after the Act. No. 6. Contributions and Benefits. Working Men. No. 7. Women under the Insurance Act. No. 15. Voluntary Contributors. No. 8 Benefits No. 9. Questions and Answers for Members of Trade Unions. No. 16. Domestic Servants. No. 17. Girls under 21 in Domestic Service. The Leaflets may be obtained from any Customs and Excise Officer free of charge. 345/3/2/1